From microverse to metaverse : modelling the future through today's virtual worlds - Evans, Leighton, 1979-; Frith, Jordan; Saker, Michael (Emerald points., 2022)
From Microverse to Metaverse: Modelling the Future through Today's Virtual Worlds analyzes the political economy of emerging tech with the mechanisms of identity and behavioral constraints involved to map what a metaverse might be like, whether it can happen, and just why some companies seem so determined to make it happen.